A new method for testing the interfacial shear properties between rock and early-aged shotcrete (Fracture and Structural Integrity, 2019)
A new method for testing the interfacial shear properties between early-aged shotcrete and rock was developed in the present study, which was proposed following a new test principle. A new set of mould was also designed and described in detail, as well as the test procedures. The main advantages of the new method was that, the shock and vibration could be eliminated compared with the traditional ones, and made the evaluation on the shear properties of the very early-aged rock-shotcrete interface possible. With the newly developed method, the time-dependent rock-shotcrete interfacial shear properties were addressed. It was found that, the time-dependent shear behaviours of the interface could be regressed by a 3-parameter exponential function with high accuracy. In general, the presented research focused on the description and verification of the new test method, which could provide a new way to evaluate the interfacial shear properties between very early-aged shotcrete and rock for numerical simulations and other uses.
Keywords: Shotcrete-rock interface; New test method; Direct shear test; Time-dependent behaviors; Interfacial shear properties